Komunikasi Guru BK Dalam MeningkatkanMotivasi Belajar Siswa (Studi Pada SMP Negeri 3 Denpasar) - Belinda, Indita; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT   SMP Negeri 3 Denpasar is one of the high-quality schools. It is proven by its achievements. Motivation to learn is one of the important factors which affects students’ academic performance. In the current study, school guidance counselors at SMP Negeri 3 Denpasar play a necessary role in enhancing students’ motivation to learn. Therefore this study aims to find out the communication of school guidance counselor in enhancing students’ motivation to learn. Descriptive qualitative method was applied to explain the communication process between teachers and students. Data were obtained from a direct and deep interview with the informants. Based on the analysis, it was obtained that school guidance counselors built their credibility as sources of communication through guidance and counseling subject at school. The type of communication which more often occurred was interpersonal because it was considered more effective .   Keywords: Communication, interpersonal communication, motivation to learn,  school guidance counselor